Modelling a Strategy for Accelerating Halal Certification for MSMEs from The Perspective of Maslahah Mursalah - Dalilatud Diniyah; Fajar; Faizal Amir; Elfira Maya Adiba; Achmad Badarus Syamsi (Fakultas Syariah IAIN madura, 2025)
This study aims to determine the strategy for accelerating halal certification for Micro, Small, and Medium Enterprises (MSMEs) in Bangkalan Regency using the Analytical Hierarchy Process (AHP) method, as well as to examine the strategy from the perspective of maslahah mursalah in order to provide maximum benefits for MSME actors and the wider community. This type of research is qualitative using the AHP (Analytical Hierarchy Process) approach with the research subjects of the Ministry of Religion, MUI, Halal Center UTM, Cooperative Office. The data used are primary data and secondary data with data collection techniques using interviews and questionnaires. Based on AHP analysis, the criteria that are very influential in the process of accelerating halal certification strategies in Bangkalan are the role of halal certification bodies, which obtained the highest weight of 0.514, compared to market demand with a weight of 0.280, awareness of business actors with a weight of 0.138, and the role of government with a weight of 0.068. From the perspective of maslahah mursalah, these strategies not only aim to fulfill the immediate needs of MSMEs and consumers for halal assurance but also serve the broader public interest by promoting social welfare, economic justice, and community trust. By prioritizing the role of halal certification bodies and enhancing awareness through socialization programs, the approach ensures that the certification process is efficient, transparent, and inclusive. This aligns with the principle of maslahah mursalah, which advocates for solutions that bring maximum benefit and prevent harm to society.